Reversible visual recovery in Optic Neuritis patient with No Light Perception VA: Poster Presentation - Case Report - Ophthalmologist - DEVI PUTRI SWADAYANI; Irwan sanjaya (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction : Optic neuritis is characterized by an inflammation and demyelination of the optic nerve and is traditionally treated with corticosteroids. The findings of the ONTT, reported in more than 50 publications during the past 20 years, have numerous implications Case Illustration : A 48-year-old woman presented to the ophthalmology outpatient clinic with a 12-day history of blurred vision. The best-corrected visual acuities and Ishihara colour vision was unilaterally reduced with a non light perception on left eye. There were also relative afferent pupillary defect with slow respons of pupillary reflect. Slit-lamp examination was otherwise normal. Funduscopy was Papillary edema on left eye, with all quadrant blurry edge. Optic neuritis (ON) was presumed as she had suffered with this previously. She was hospitalized and undergone (optic neuritis treatment trial) ONTT . Thereafter, a trial of pulsed methylprednisolone was commenced, resulting in near complete resolution of the Visual acuity that become 6/40 UCVA from NLP. Discussion : The original ONTT, along with three follow-up studies at five-year intervals, generated more than three dozen papers in scientific journals. Collectively they show what happens to an individual over the course of 15 years following about of optic neuritis. Conclusion : Prior to the ONTT well-established guidelines for treating optic neuritis did not exist, this case were demonstrates the importance of keep starting ONTT with a point valuable to patient with NLP.